2003
DOI: 10.1007/s00122-002-1115-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolate-specific QTLs of resistance to leaf stripe (Pyrenophora graminea) in the 'Steptoe' × 'Morex' spring barley cross

Abstract: Leaf stripe caused by the fungus Pyrenophora graminea represents a serious threat to grain yield in organically grown barley and in conventional Nordic and Mediterranean districts, for which resistant cultivars are necessary. A medium-density, molecular marker map derived from a 'Steptoe' (partially resistant) x 'Morex' (susceptible) spring barley cross and its derived doubled-haploid mapping population inoculated with the fungus made it possible to identify QTLs of resistance to leaf stripe. In order to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 22 publications
1
47
1
1
Order By: Relevance
“…These studies have focused on biotrophic pathogens, where qualitative race-specific resistance conferred by major resistance genes is vulnerable to changes in the genetic composition of the pathogen population. The identification of both broad-spectrum and isolate specific resistance QTL suggests that significant variation for mechanisms of pathogenesis exists within many pathogen species and that qualitative isolate-specific resistance conferred by major resistance genes accounts for only a portion of plant defense against naturally variable pathogen populations (Caranta et al 1997;Arru et al 2003;Calenge et al 2004;Talukder et al 2004;Diener and Ausubel 2005;Jorge et al 2005). Understanding differences and similarities in mechanisms of partial or quantitative resistance to pathogens of different lifestyles, including biotrophs and necrotrophs, is vital to developing long-term strategies for pathogen control in a complex environment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have focused on biotrophic pathogens, where qualitative race-specific resistance conferred by major resistance genes is vulnerable to changes in the genetic composition of the pathogen population. The identification of both broad-spectrum and isolate specific resistance QTL suggests that significant variation for mechanisms of pathogenesis exists within many pathogen species and that qualitative isolate-specific resistance conferred by major resistance genes accounts for only a portion of plant defense against naturally variable pathogen populations (Caranta et al 1997;Arru et al 2003;Calenge et al 2004;Talukder et al 2004;Diener and Ausubel 2005;Jorge et al 2005). Understanding differences and similarities in mechanisms of partial or quantitative resistance to pathogens of different lifestyles, including biotrophs and necrotrophs, is vital to developing long-term strategies for pathogen control in a complex environment.…”
Section: Discussionmentioning
confidence: 99%
“…During seed germination, its growing mycelium penetrates the coleorhiza and it colonizes the plant systemically starting from the root tip (Haegi et al, 1998). The disease is particularly acute in Mediterranean's winter barley districts, where soil temperatures below 12 • C during seed germination promote the infection of the rootlet (Arru et al, 2003). The typical symptoms, spike sterility and chlorotic stripes on leaves, which gradually extend to the full length of the leaf and finally become necrotic, lead to severe yield reductions when seed infection is high (Delogu et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Resistance genes are therefore desirable for controlling leaf stripe disease. Both polygenic partial resistance (Skou and Haar 1987;Pecchioni et al 1996;Arru et al 2002Arru et al , 2003a) and race-specific resistance genes have been identified. Rdg1a, conferring complete resistance to a subset of P. graminea isolates, has been mapped on the long arm of barley chromosome 2 (2H) (Giese et al 1993; Thomsen et al 1997).…”
Section: Introductionmentioning
confidence: 99%